RELATIONSHIPS OFPHOSPHORUSFORMS INSEDIMENTS OF FUBAO GULF, LAKE DIANCHI, CHINA - F. X. Chen; S. Y. Lu; X. C. Jin; J. N; Guo (Journal of Animal and Plant Sciences, 2015)
Phosphorus (P) forms found in lake sediments provide information that is important for eutrophication control. Contents of nine kinds of phosphorus forms in five top-layer (0–10 cm) sediment samples collected from Lake Dianchi, China were investigated. Inorganic phosphorus (I-P) comprised 62.3–78.2% of TP in these samples, owing to the low level of aquatic life caused by the high content of external pollutant sources and the low water exchange rate of once annually. Algae significantly deplete sedimentary P, resulting in low BAP forms in the sediment. Aluminum (Al) and manganese (Mn) oxides and iron hydroxides (Fe-P), organic phosphorus (Org-P),and calcium-bound P (Ca-P) were significantly correlated with TP content in the top sediment layers. The correlation between I-P and Fe-P content was also significant in these layers. All BAPs showed low correlation with Org-P. It was concluded that the bioavailability of TP in sediment is affected by inflow and anthropogenic activities. The P species and contents in the sediments are useful for the cognition of environmental geochemical behavior of P in the sediment of Dianchi Lake, and this is of great importance for the pollutant load, especially the internal load, control and environmental restoration of Lake Dianchi.
Keywords: Bioavailable phosphorus; Correlation; Lake Dianchi; Phosphorus forms; Sediment